Análisis de factores urbanos que definen la vulnerabilidad de los espacios públicos de la ciudad de Guaranda, propuesta urbano-arquitectónica - Gutiérrez Barragán, Sofía Natalia (2025)
The analysis of the mobility of vulnerable social groups in the plazas and parks of Guaranda city is a crucial research topic to understand and address the needs of these groups within urban environments. This study examines how vulnerable individuals such as older adults, children, people with disabilities, or those living in poverty interact with public spaces in Guaranda, specifically plazas and parks. The research involves direct observation, surveys, and interviews to identify the challenges these groups face when accessing and using these urban spaces. Factors such as physical accessibility, safety, availability of basic services, and the perception of belonging and inclusion are analyzed. Based on the findings of the analysis, an urban-architectural intervention is proposed to improve the experience and participation of vulnerable groups in Guaranda’s plazas and parks. This may include the installation of wheelchair ramps, accessible rest areas, adequate lighting, clear signage, and additional safety measures. Moreover, social inclusion programs and specific activities could be suggested to promote integration and equitable enjoyment of these spaces by all citizens. In summary, this study not only aims to understand the mobility challenges faced by vulnerable groups in specific urban settings, but also to propose concrete and practical solutions to enhance their quality of life and participation in community life.